Crystal structure and Hirshfeld surface analysis of 5-methyl-1,2,4-triazolo[1,5-a]pyrimidine - Lahmidi, Sanae (Acta Crystallogr E Crystallogr Commun, 2018)
The nine-membered ring system of the title compound, C(6)H(6)N(4), is essentially planar. In the crystal, molecules are linked via C—H(Trz)⋯N(Trz) and C—H(Pyrm)⋯N(Trz) (Trz = triazole and Pyrm = pyrimidine) hydrogen bonds together with weaker C—H(Pyrm)⋯N(Pyrm) hydrogen bonds to form layers parallel to ([Image: see text]02). The layers are further connected by π–π-stacking interactions between the nine-membered ring system [centroid–centroid = 3.7910 (8) Å], forming oblique stacks along the a-axis direction. The Hirshfeld surface analysis of the crystal structure indicates that the most important contributions for the crystal packing are from H⋯N/N⋯H (40.1%), H⋯H (35.3%), H⋯C/C⋯H (9.5%), N⋯C/C⋯N (9.0%), N⋯N (3.1%) and C⋯C (3.0%) interactions and that hydrogen-bonding and van der Waals interactions are the dominant interactions in the crystal packing. No significant C—H⋯π interactions are observed.